ANALISIS DAN MINIMASI WASTE PADA AREA PRODUKSI PT. XYZ DENGAN PENDEKATAN LEAN MANUFACTURING DAN SIMULASI SISTEM - Hayati, (2022)
PT. XYZ is a manufacturing company engaged in the manufacture of packaging boxes, namely in the form of cardboard packaging for cosmetic tools, helmets, medicines and so on. In the production process at PT. XYZ still found waste especially in defects, waiting and excessive transportation. This study aims to minimize or eliminate waste as an activity that does not provide added value by providing recommendations for improvement using a lean manufacturing approach, then the improvement recommendations are designed through system simulation using proModel software. The lean manufacturing method used in this research is Value Stream Mapping (VSM) to map the entire value stream in the production process from start to finish, where the manufacturing process is supported based on the tools selected from the Value Stream Analysis Tools (VALSAT). Furthermore, to find the root cause of the occurrence of waste fishbone diagrams are used and to determine the causes of the most impactful or most critical waste, the Failure Mode and Effects Analysis (FMEA) method is used, then multiple linear regression analysis is carried out to validate and find out how much influence the causal factors give waste to waste itself. The results showed that with the recommendations for improvement given, the time of the production process for making cardboard packaging at PT. XYZ can be reduced from 9743.70 seconds to 6417.15 seconds and based on the simulation results, it shows an increase in the average number of production per month which is 64.26% with an increase from 52962 pcs to 87000 pcs.